(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This article examines the current problem of forming the foundations of tolerant attitudes in preschool children in the context of the modern educational paradigm. The author analyzes the possibilities of an integrative approach that allows combining the cognitive, emotional-value, and behavioral components of a child’s personality into a single socialization process. Special attention is paid to the concept of "cultural dialogue" as a basic pedagogical tool. The work substantiates that through contact with the diversity of cultural codes (traditions, folklore, ethical norms), not only knowledge accumulation occurs, but also the formation of a "primary image of the world" free from prejudice. The article details the pedagogical conditions that ensure the transition from a passive perception of information to an active position of the intercultural communication subject.